2006
DOI: 10.1163/156856106779116623
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatments of wood–plastic composites (WPCs) to improve adhesion

Abstract: In an effort to improve the adhesive bonding between wood-plastic composites (WPCs) formulated with polypropylene and a commercial epoxy adhesive, surface treatments were performed to chemically and/or physically modify the surface of WPCs. The treatments were performed on extruded WPC that had been planed and consisted of chromic acid treatment, flame treatment, water treatment, flame then water treatment and water then flame treatment. The strength of the adhesive bonds of the treated samples was tested foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 11 publications
0
39
0
2
Order By: Relevance
“…Although difficult to quantify, a fine dispersion was observed by microscopy for all cross-sections with no apparent fiber bundles or agglomerates. For matrix systems composed of non-polar polymers with limited affinity to the fiber surface 20 , the fibers tend to agglomerate and form cluster of fibres, which act as stress concentrations and reduce the strength of the composite. It is therefore desirable to avoid fiber agglomeration.…”
Section: Interface and Fiber Dispersionmentioning
confidence: 99%
“…Although difficult to quantify, a fine dispersion was observed by microscopy for all cross-sections with no apparent fiber bundles or agglomerates. For matrix systems composed of non-polar polymers with limited affinity to the fiber surface 20 , the fibers tend to agglomerate and form cluster of fibres, which act as stress concentrations and reduce the strength of the composite. It is therefore desirable to avoid fiber agglomeration.…”
Section: Interface and Fiber Dispersionmentioning
confidence: 99%
“…In this study, the combined treatment for polyethylene WPCs of sanding then coating with a silane coupling agent, followed by plasma discharge, was utilized to achieve a fast treatment method and a satisfactory bonding performance. Gramlich et al (2006) combined flame and water surface treatments to treat the surface of WPCs. The experimental results showed that the combined treatment of the composites obtained a better bonding performance, and the combination of the two methods may appear as an unexpected combined action.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the polyethylene ingredient present within the polyethylene WPCs results in poor polarity, lower surface energy, and difficult adhesion of the composites (Tahara et al 2003;Gramlich 2006;Liu et al 2010). Hence, a surface treatment is necessary for the polyethylene WPCs to obtain optimal bonding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the individual surface treatments mentioned, a combined treatment was also employed to treat the WPCs materials. For example, Gramlich et al (2006) combined flame and water surface treatments to treat the surface of the WPCs. Moghadamzadeh et al (2011) employed a combination treatment of sanding followed by a corona discharge treatment to improve the bonding strengths of the WPCs.…”
Section: Introductionmentioning
confidence: 99%